Feasibility of a group cessation program for co‐smokers of cannabis and tobacco. (11th February 2015) - Becker, Julia; Haug, Severin; Kraemer, Thomas; Schaub, Michael P.
Abstract Introduction and Aims This study aims to evaluate the feasibility and effects of a group cessation program for cannabis and tobacco co‐smokers. Design and Methods Using a repeated‐measures design with pre‐, post‐ and six months follow‐up assessments, feasibility (intervention utilisation, safety and acceptability) and changes in substance use behaviour and mental health were evaluated. The intervention consisted of five to six group sessions and was based on current treatment techniques (e.g. motivational interviewing, cognitive‐behavioural therapy, and self‐control training). In total, 77 adults who used cannabis at least once weekly and cigarettes or similar products at least once daily participated in the study. Results Within nine months, the target sample size was reached. Treatment retention was 62.3%, and only three participants discontinued treatment due to severe problems (concentration problems, sleeping problems, depressive symptoms, and/or distorted perceptions). In total, 41.5% and 23.4% reported abstinence from cigarettes, cannabis or both at the end of treatment and the follow‐up, respectively. The individual abstinence rates for cigarettes and cannabis were 32.5% and 23.4% (end of treatment) and 10.4% and 19.5% (follow‐up), and 13% (end of treatment) and 5.2% (follow‐up) achieved dual abstinence validated for tobacco abstinence. Over the study period, significant decreases in tobacco and cannabis use frequencies and significant improvements in additional outcomes (drinking problems, symptoms of cannabis use disorder, nicotine dependence, depression and anxiety) were achieved. Discussion and Conclusions The evaluated intervention for co‐smokers is feasible regarding recruitment, intervention retention and safety. The promising results regarding substance use and mental health support a randomised controlled trial to evaluate effectiveness. [Becker J, Haug S, Kraemer T, Schaub MP. Feasibility of a group cessation program for co‐smokers of cannabis and tobacco. Drug Alcohol Rev 2015;34:418–426]